GEOINFORMATION METHODS IN THE MAPPING OF THE ISLANDS OF THE NORTH-WESTERN PART OF THE CASPIAN SEA - M. M. Kuramagomedov; G. M. Abdurakhmanov; A. G. Abdurakhmanov; A. A. Teimurov; G. M. Nakhibasheva; N. S. Kurbanova; N. M. Melikova; A. A. Grikurova; U. U. Ivanushenko (Юг России: экология, развитие, 2014)
The article dealt with the possibilities of the methods of geoinformation mapping to study peculiarities of the Islands Chechen and Tuleny. Also in the article presents a technique of drawing up of digital base maps and the creation of the base of thematic layers to create a geinformation system.